Marketing Management in the System of Agricultural Enterprises Management - Кучер, О. В.; Покотильська, Н. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The functioning of agricultural enterprises in modern conditions require timely management adaptation to external changes; which in turn necessitate the use of marketing management in production administration and sales. Marketing management in its essence is a set of rules for making decisions which companies use in its activities. It was analyzed the category "Marketing Management" from the point of view of the foreign and Ukrainian scientists. Based on studied literature it was defined the essence of marketing management; its place and role in the overall company management. It was verified the economic efficiency of agricultural enterprises in the context of marketing management. It was determined the necessity of the modern approach to management of agricultural enterprises; embodying the new philosophy of governance and its implementation on a new level.